Uwarunkowania polityki zdrowotnej powiatu grodzkiego (na przykładzie Gdańska) - Michalski, Tomasz (Space – Society – Economy, 2009)
The main aim of the study is to present the determinants of conducting health policy by the self-government of a city county. Conceptually, the model of a territorial social system was used a basis. Health policy conducted by city county self-governments is secondary to the one enacted by systems of a higher rank (mainly province divisions of the National Health Fund. If primarily focuses on prophylactic programmes. Programmes directed at fighting alcoholism and drug addiction are exceptions from this rule. At the background of other types of local governments, the self-government of city counties is in the best position for two reasons. Firstly, it realises tasks insofar as health policy being under management of both counties and communes. Thus in its policy it must take into consideration only the province government and central level institutions (or their branches). Secondly, in most cases the local government of city counties administers big towns and cities which have a developed so-called material. background of health service venues. This gives a greater freedom in creating tasks for health policy.